PKM Kewirausahaan Pembuatan Kerajinan Tangan Bunga Rajut - Pahrul Pahrul; Hasbi Hasbi; Ika Wisudawaty; Muh. Rizah Putrawan; Mohamad Ikbal Riski A. Danial (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
Knitted flowers are a beautiful result of creativity and the skill of one's hands. Making knitted flowers can be a relaxing and creative activity option. Knitted flowers can be done using knitting techniques ranging from easy techniques to quite complex techniques, then producing beautiful accessories such as a series of knitted flowers that stand out with the characteristic knitted flowers that are woven in detail. Apart from that, knitted flower bouquets can also be made using the crochet technique which creates a flower bouquet that is not only attractive from an aesthetic perspective, but also lasts longer than real flowers. These knitted flowers are also often the focus of attention at various special and special events, and can be used as a unique and memorable gift for friends, relatives, co-workers or loved ones.